Oxford correspondence workbook - Ashley, A. (Oxford University Press, 2003)
Contents: Letters, faxes.and emails; Content and style; Enquiries; Repliesand quotations; Orders; Payment; Complaints and adjustments; Credit; Banking; Agentsandagencies so; ransportationandshipping Insurance; Miscellaneouscorrespondence; Memosandreports; Personnelappointments